Gender Matters: A Multilevel Analysis of Gender and Voice at Work. (23rd March 2021) - Cooper, Rae; Mosseri, Sarah; Vromen, Ariadne; Baird, Marian; Hill, Elizabeth; Probyn, Elspeth
Abstract: The role of gender in shaping a range of work experiences and outcomes is well documented, yet there remains limited knowledge of the gendered dimensions of voice. In addressing the understudied topic of gender and voice, we propose a multilevel framework for analysing the relationship, which goes beyond thinking of gender only in terms of individual‐level gender identities. We conceptualize gender at three levels – as embedded in individual identities, in organizational policies and practices and in labour market segmentations – and show that gender, at each level, is associated with variations in worker voice opportunities and practices. We test our model using data from a mixed‐methods Australian study that consisted of a national survey with young working women and men and a series of targeted focus groups with young working women. We find no individual‐level differences in women's and men's reported voice, measured as managerial consultation and as perceived influence over workplace matters. However, we do find a diminished voice among both women and men employed within specific gendered work environments, namely in organizations where workers perceive high levels of gender inequality and in women‐dominated industries. Qualitative findings provide additional detail on how women's voice materializes and is constrained within gendered work settings.